2013
DOI: 10.5380/rber.v2i4.35793
|View full text |Cite
|
Sign up to set email alerts
|

Efeito das geadas em culturas energéticas

Abstract: O conhecimento dos efeitos de fenômenos climáticos extremos, como as geadas em diversas culturas é de grande importância para o zoneamento climático visando à otimização dos resultados de produção. As fontes de energias alternativas e a utilização de biodisel vêm abrindo um mercado promissor para as culturas energéticas como Pinhão manso, Girassol, Eucalipto e outras, portanto se faz necessário estabelecer relações entre as culturas e os efeitos fisiológicos que as geadas podem causar a estas. Deste modo, o pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For each plant species there is a temperature at which protoplasm freezing will occur and may occur before the air temperature reaches 0°C. Some species may have a higher resistance to freezing, remaining alive even after the phenomenon has occurred, but mortality may occur in younger tissues, such as the apex (Perissato et al 2013). Kreyling et al (2015) observed a cold tolerance of up to -9.2°C for Sequoia sempervirens.…”
Section: Discussionmentioning
confidence: 99%
“…For each plant species there is a temperature at which protoplasm freezing will occur and may occur before the air temperature reaches 0°C. Some species may have a higher resistance to freezing, remaining alive even after the phenomenon has occurred, but mortality may occur in younger tissues, such as the apex (Perissato et al 2013). Kreyling et al (2015) observed a cold tolerance of up to -9.2°C for Sequoia sempervirens.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the large impact that frosts have upon the agriculture, numerous scientific studies have centred on addressing the damage caused by this phenomenon to: coffee (Androcioli Filho and Caramori, 2000), peaches (Szewczuk et al, 2007), sugar cane (Monteiro and Sentelhas, 2014), corn (Carter, 1995), beans (Meyer and Badaruddin, 2001), apples (Eccel et al, 2009), vines (Brixner et al, 2014) and canola (Perissato et al, 2013), among other crops. Minimizing frost damage can be done by taking preventive measures (passive protection) or by acting during the frost (Snyder and de Melo-Abreu, 2005).…”
Section: Introductionmentioning
confidence: 99%